Emotion beyond boundaries: How multimodal cues foster cross-cultural affective contagion in immersive livestreaming - Yu Zhang; Yuanyuan Liu; Haoran Mao; Junxiang Zhao (PLoS ONE, 2026)
Digital and intelligent media technologies are fundamentally reshaping the landscape of international communication. This study examines the multimodal emotional communication mechanisms and efficacy of immersive live streaming through a case analysis of American influencer IShowSpeed’s “China tour” broadcasts on Bilibili. Using network analysis to map user interactions, sentiment analysis to measure emotional responses, and epidemiological modeling to track emotion spread, this study investigates how emotions operate and spread in cross-cultural digital environments. Our findings reveal three interconnected mechanisms: (1) algorithm-driven decentralized network structures that facilitate rapid information diffusion, (2) multimodal sensory cues triggering high-arousal positive emotions, and (3) emotion-similarity-based multilevel contagion pathways enabling cascading effects. These mechanisms collectively constitute a nonlinear, affect-first communication paradigm that effectively orchestrates immersive experiences and emotional resonance across cultural boundaries, generating positive cascading effects among diverse audiences. This research contributes to the theorization of digital international communication by proposing an exploratory “algorithm-infrastructure, emotion-pathway, identification-outcome” framework derived from a single-case mechanism analysis, and by offering empirical insight into how cross-cultural engagement is shaped through the interaction of affective communication and platform dynamics.